Exome Analysis Identifies a Novel Compound Heterozygous Alteration in TGM1 Gene Leading to Lamellar Ichthyosis in a Child From Saudi Arabia: Case Presentation - Alallasi, Sami Raja; Kokandi, Amal A.; Banagnapali, Babajan; Shaik, Noor Ahmad; Al-Shehri, Bandar Ali; Alrayes, Nuha Mohammad; Al-Aama, Jumana Yousuf; Jelani, Musharraf (Frontiers in Pediatrics, 2019)
ABSTRACT Background: Lamellar ichthyosis is an autosomal recessive type of rare skin disorders characterized with defective epidermis leading hyperkeratosis with brownish-grey scales over the body. These patients are born as collodion babies and may also exhibit additional features like erythema, ectropion, and eclabium. This disease is mainly caused by homozygous and compound heterozygous alterations in transglutaminase 1 encoding gene (TGM1), which is located on 14q12. Case presentation: This study reports the genetic analysis of a four-year Saudi girl presenting lamellar ichthyosis. She was the first child of unrelated parents. The family had no previous history of the disease phenotype. She was born as a collodion baby without any prenatal complications. At the time of this study she had developed rough scaly skin on her legs, arms and trunk regions with thick palms and soles. Whole exome sequencing (WES) followed by Sanger sequence validation identified a novel compound heterozygous variant in TGM1 gene. The paternal variant was a missense transition (c.1141G>A; p.Ala381Thr) present at exon 7, while maternal variant (c.758-1G>C) was present at the intron4-exon5 boundary. To the best of our knowledge these variants had not been reported before in TGM1 gene. Conclusion: In isolated and inbred populations, homozygous variants are identified more frequently; however, our results suggest that compound heterozygous variants should also be considered especially when the marriages are not consanguineous.